(untitled) - Garber, Nicholas J. (Australia, 2015)
Focuses on giving students insight into all facets of traffic and highway engineering. This text uses pedagogical tools such as worked problems, diagrams and tables, reference material, and realistic examples to demonstrate how the material is applied.
Keywords: Kỹ thuật đường bộ,Highway engineering,Traffic engineering,Kỹ thuật giao thông